2002
DOI: 10.1136/jcp.55.6.472
|View full text |Cite
|
Sign up to set email alerts
|

A survey of vaccine coverage and antibiotic prophylaxis in splenectomised patients in Scotland

Abstract: Aims: To determine the coverage of vaccine and antibiotic prophylaxis in splenectomised patients in Scotland. Methods: Patients who had undergone splenectomy between 1 January 1988 and 31 December 1998 were identified. A questionnaire was sent to general practitioners to validate vaccine and antibiotic status for these patients.Results: A total of 974 living splenectomised patients were identified during the study period. Information on vaccine and antibiotic status was available for 708 (73%) and 770 (79%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 5 publications
1
14
0
5
Order By: Relevance
“…The audit by Kyaw et al showed that only half of patients received information about antibiotic prophylaxis 9. Each patient should carry at all times a letter or card documenting the splenectomy and should wear a bracelet or pendant to signal their status to doctors and other healthcare staff.…”
mentioning
confidence: 99%
“…The audit by Kyaw et al showed that only half of patients received information about antibiotic prophylaxis 9. Each patient should carry at all times a letter or card documenting the splenectomy and should wear a bracelet or pendant to signal their status to doctors and other healthcare staff.…”
mentioning
confidence: 99%
“…Pnömokok aşısı, çalışma kapsamında değerlendirilen olguların %62,7'sine operasyon öncesi, %23,5'ine operasyon sonrası uygulanmışken, Görkem ve arkadaşlarının çalışmasında [9] olguların %87,1'ine operasyon öncesi %12,9'una operasyon sonrası, Özkören ve arkadaşlarının çalışmasında [8] olguların %41'ine operasyon öncesi %33,3'üne operasyon sonrası yapıldığı görülmüştür. Ayrıca pnömokok aşısı Kyaw ve arkadaşlarının çalışmasında [17] olguların %88'ine uygulanmışken, bu oran Langley ve arkadaşlarının çalışmasında [18] %16,5 olarak belirlenmiştir. Ülkemizde yapılan çalışmalarda H. influenzae tip B konjuge aşısının ve meningokok aşısının uygulama oranları hakkında veriler bulunmazken, H. influenzae tip B konjuge aşısı sunulan çalışmada olguların %72,6'sına, Kyaw ve arkadaşlarının çalışmasında [17] %70'ine ve Langley ve arkadaşlarının çalışmasında [18] ise %53,1'ine uygulanmıştır.…”
Section: Discussionunclassified
“…Ayrıca pnömokok aşısı Kyaw ve arkadaşlarının çalışmasında [17] olguların %88'ine uygulanmışken, bu oran Langley ve arkadaşlarının çalışmasında [18] %16,5 olarak belirlenmiştir. Ülkemizde yapılan çalışmalarda H. influenzae tip B konjuge aşısının ve meningokok aşısının uygulama oranları hakkında veriler bulunmazken, H. influenzae tip B konjuge aşısı sunulan çalışmada olguların %72,6'sına, Kyaw ve arkadaşlarının çalışmasında [17] %70'ine ve Langley ve arkadaşlarının çalışmasında [18] ise %53,1'ine uygulanmıştır. Meningokok aşısı da bu çalışmada olguların %72,6'sına uygulanmışken, Kyaw ve arkadaşlarının çalışmasında [17] %51'ine uygulanmıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The presence of intracellular bacteria or morulae Newland 85 underlines that in his experience he has noted that only a very low rate of patients (13%) received all three vaccines before elective splenectomy and suggests that each patient undergoing splenectomy should carry a letter or a card to signal their status. Kyaw et al 86 showed that only half of patients received information about antibiotics prophylaxis.…”
Section: Treatmentmentioning
confidence: 99%